2009
DOI: 10.3892/ijo_00000188
|View full text |Cite
|
Sign up to set email alerts
|

The tumor antigens RHAMM and G250/CAIX are expressed in head and neck squamous cell carcinomas and elicit specific CD8+ T cell responses

Abstract: Abstract. Despite advances in surgery, radio-and chemotherapy, therapeutic approaches for patients with head and neck squamous carcinoma (HNSCC) need to be improved. Immunotherapies eliciting tumor specific immune responses might constitute novel treatment options. We therefore investigated the expression and immunogenicity of two tumor-associated antigens (TAA) the receptor for hyaluronic acid mediated motility (RHAMM) and carboanhydrase IX (G250/CAIX) in HNSCC patients. Twenty-two HNSCC samples were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…29 Hydroxylation of either human HIF-1α Pro 402 or Pro 564 promotes the interaction with pVHL, leading to the recruitment of ubiquitin complexes and degradation of HIF-1α. 12 FIH-1 was initially identified as a protein binding to HIF-1α and VHL and regulating the transcriptional activity of HIF-1. 24 Lando et al 30 showed that FIH-1 is an asparaginyl hydroxylase that regulates the transcriptional activity of HIF-1 by hydroxylating Asn 803 .…”
Section: Nicd3 Mutant Defective In Putative Vhl Binding Represses Thementioning
confidence: 99%
See 1 more Smart Citation
“…29 Hydroxylation of either human HIF-1α Pro 402 or Pro 564 promotes the interaction with pVHL, leading to the recruitment of ubiquitin complexes and degradation of HIF-1α. 12 FIH-1 was initially identified as a protein binding to HIF-1α and VHL and regulating the transcriptional activity of HIF-1. 24 Lando et al 30 showed that FIH-1 is an asparaginyl hydroxylase that regulates the transcriptional activity of HIF-1 by hydroxylating Asn 803 .…”
Section: Nicd3 Mutant Defective In Putative Vhl Binding Represses Thementioning
confidence: 99%
“…7 These antitumor mechanisms are not exploited by the classic cancer drugs and therefore represent a new anticancer drug discovery strategy. Overexpression of CA9 is consistently seen in a high proportion of carcinomas of the cervix, 8 clear cell carcinoma of the kidney, 9 and to a lesser extent in breast cancer, 10,11 carcinoma of the head and neck, 12,13 lung cancer, 14 and tumors of the brain. 15,16 Elevated expression of CA9 during hypoxia is suggestive of its importance during tumor adaptation to hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a phase I vaccination trial was initiated in which patients developed specific CTL response after 4 vaccinations (22). Similar results were obtained in patients with chronic lymphocytic leukemia and tumors of the head/neck region (35).…”
Section: Discussionmentioning
confidence: 64%
“…A previous CD168 knockdown study demonstrated growth reduction of transplanted tumors (28). Increased CD168 expression was revealed to be indicative of an elevated, or abnormal, level of cell proliferation in human OSCC (17).…”
Section: Discussionmentioning
confidence: 80%
“…), and is essential in cell migration and proliferation during embryogenesis (12). CD168 has been extensively studied in different tumor cell lines and a variety of tumor types, including lymphoid and myeloid malignancies, and colorectal, breast, ovarian and urothelial carcinoma (13)(14)(15)(16), although only a few studies have dealt with its expression and significance in the head-and-neck SCCs (17)(18)(19). It has been demonstrated that CD168 is required to facilitate proliferation of head-and-neck cancer cells (18).…”
Section: Introductionmentioning
confidence: 99%